Pemahaman Nos Peserta Didik Sekolah Dasar - Hana Lestari; Ima Rahmawati (PUSAT SAINS INDONESIA, 2020)
This study aims to determine differences understanding of Nature of science (NoS) elementary school students before and after using the Nature of science (NoS) learning model. The method used is a pre-experiment with one group pretest postest design. The instrument used was the NoS understanding questionnaire and observation sheet. The collected data was analyzed by quantitative descriptive. The results of this study indicate students' initial understanding of NoS with a percentage of 84% in the good category and after learning with the NoS model with a percentage of 89% in the very good category. Seen from the lowest aspect of Nos is students' understanding of law and theory. After t-test, it can be concluded that there are differences in students' understanding of NoS before and after using NoS learning.